(untitled) (Journal of the College of Basic Education, 2022)
Romanticism; It is such an important political, social and ideological artistic revolution, which occupied a part of the XIX century and much of the XX century in Europe and much of the world, still according to many literary books today are many of its manifestations and aspects such as; Freedom, Individualism (individual), Democracy, Nationalism ... etc. Romanticism was characterized by its emphasis on emotion and individualism as well as glorification of all the past and nature, the latter also being celebrated. It was partly a reaction to the Industrial Revolution, the aristocratic social and political norms of the Age of Enlightenment, and the scientific rationalization of nature. It was embodied most strongly in the visual arts, music, and literature, but had a major impact on historiography, education, and the natural sciences. It had a significant and complex effect on politics, and while for much of the Romantic period it was associated with liberalism and radicalism, its long-term effect on the growth of nationalism was perhaps more significant. The Arab world pass for many years in decline which included all walks of life, including political, economic, social and even literature which for those not far from this phase of the dark history of the Arab world, it began looming features of a new era, in poetry began to explore the limits of the classical qasida, although he remained a clearly neo-classical, then to explore themes of anticolonialism as well as the classical concepts and new kinds of literature such as novels, short stories . The Mahjar poets included other writers, in South America as well as the USA, further contributed to the development of the forms available to Arab poets.